A paradigm shift to CO2 sequestration to manage global warming – With the emphasis on developing countries - Bhattacharyya, Siddhartha Shankar; Leite, Fernanda Figueiredo Granja Dorilêo; Adeyemi, Maxwell Adebayo; Sarker, AhadJahin; Cambareri, Gustavo Sebastián; Faverin, Claudia; Tieri, Maria Paz; Castillo Zacarías, Carlos; Melchor Martínez, Elda; Parra Saldivar, Roberto; Iqbal, Hafiz M. (Elsevier, 2021)
Global land use changes that tend to satisfy the food needs of augmenting population is provoking agricultural soils to act as a carbon (C) source rather than sink. Agricultural management practices are crucial to offset the anthropogenic C emission; hence, Carbon sequestration (CS) in agriculture is a viable option for reversing this cycle, but it is based on hypotheses that must be questioned in order to contribute to the development of new agricultural techniques. This review summarizes a global perspective focusing on 5 developing countries (DC) (Bangladesh, Brazil, Argentina, Nigeria and Mexico) because of their importance on global C budget and on the agricultural sector as well as the impact produced by several global practices such as tillage, agroforestry systems, silvopasture, 4p1000 on CO2 sequestration. We also discussed about global policies regarding CS and tools available to measure CS. We found that among all practices agroforestry deemed to be the most promising approach and conversion from pasture to agroforestry will be favorable to both farmers and in changing climate, (e.g., agroforestry systems can generate 725 Euroeq C credit in EU) while some strategies (e.g. no-tillage) supposed to be less promising and over-hyped. In terms of conservative tillage (no-, reduced-, and minimal tillage systems), global and DC's land use increased. However, the impact of no-tillage is ambiguous since the beneficial impact is only limited to top soil (0–10 cm) as opposed to conventional mechanisms. Grasses, cereals and cover crops have higher potential of CS in their soils. While the 4p1000 initiative appears to be successful in certain areas, further research is needed to validate this possible mode of CS. Furthermore, for effective policy design and implementation to obtain more SOC stock, we strongly emphasize to include farmers globally as they are the one and only sustainable driver, hence, government and associated authorities should take initiatives (e.g., stimulus incentives, C credits) to form C market and promote C plantings. Otherwise, policy failure may occur. Moreover, to determine the true effect of these activities or regulations on CS, we must concurrently analyze SOC stock adjustments using models or direct measurements. Above all, SOC is the founding block of sustainable agriculture and inextricably linked with food security. Climate-smart managing of agriculture is very crucial for a massive SOC stock globally especially in DC's.